2016
DOI: 10.1111/jog.12948
|View full text |Cite
|
Sign up to set email alerts
|

Survey of prenatal testing for genetic disorders in Japan: Recent report

Abstract: Aim: In order to investigate the current status of prenatal testing for genetic disorders, we conducted a multicenter retrospective questionnaire survey. Methods: The questionnaire was sent to 105 facilities with genetic counseling systems. The questionnaire consisted of two parts: (i) the number of prenatal tests conducted for genetic disorders from January 2010 to December 2012, whether the laboratory was combined with the counseling facility or separate, the sampling procedure method, the testing results, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…In our study, molecular testing prior to conception was performed in around 50% of the potential carriers at the mean age of 30 years. The results from other countries, even with well‐organized genetic services, are also unsatisfactory …”
Section: Discussionmentioning
confidence: 99%
“…In our study, molecular testing prior to conception was performed in around 50% of the potential carriers at the mean age of 30 years. The results from other countries, even with well‐organized genetic services, are also unsatisfactory …”
Section: Discussionmentioning
confidence: 99%
“…Several case series describe the use of prenatal genetic testing for fatal or severe monogenic disorders, including spinal muscular atrophy, myotonic dystrophy type 1, b-thalassemia, and Fragile X syndrome (10)(11)(12)(13). A Japanese multicenter retrospective questionnaire survey on genetic counseling facilities showed that prenatal testing had been performed for 45 distinct genetic disorders (14). No report, however, has been issued on prenatal genetic testing of monogenic IBD.…”
Section: What Is Newmentioning
confidence: 99%
“…Thus many obstetric-gynaecologists are generally reluctant to offer the screening tests [12,13]. The system for conducting prenatal screening is underdeveloped [14], supply is limited [11] and thus uptakes for prenatal aneuploidy screening are extremely low − remaining under 5% in 2012 [13,15]. The actual uptakes rates in other East or South East Asian countries in which abortion is legal are unknown.…”
Section: Introductionmentioning
confidence: 99%